Bifurcation and degradation of geomaterials with engineering applications : proceedings of the 11th International Workshop on Bifurcation and Degradation in Geomaterials dedicated to Hans Muhlhaus, Limassol, Cyprus, 21-25 May 2017 /: proceedings of the 11th International Workshop on Bifurcation and Degradation in Geomaterials dedicated to Hans Muhlhaus, Limassol, Cyprus, 21-25 May 2017. (2017) - Unknown
No abstract available